Товариства «Просвіта» на Буковині та Західній Волині в міжвоєнний період: порівняння організаційних засад, ідейної спрямованості та діяльності - Dobrzhanskyi, Oleksandr (Видавничий дім «Гельветика», 2022)
The article compares the development of the Prosvita societies in Bukovyna and Western Volyn in the interwar period. These Ukrainian lands at that time were part of Romania and Poland. It is noted that Prosvita in Bukovyna was formed in January 1869 under the name «Ruska Besida» (Russian conversation). The society reached its greatest rise in the early 20th century in the context of Austrian liberalism. The society was not active during World War I. It did not have time to become more active during the establishment of the Ukrainian power in Bukovyna, because that period did not last long. The first Prosvita societies in Volyn were formed only in 1916 under the influence of the Ukrainian Sich Riflemen. The establishment of societies intensified during the Ukrainian revolution in 1917–1918. However, the situation changed already in 1919, when the region came under the rule of the Poles. The Polish authorities limited the activities of Prosvita societies in every possible way. It did not allow the establishment of a single centralized regional Prosvita society. It was possible to have only district organizations. Therefore, there is no need to talk about Prosvita society as a single general organization in Volyn. It was noted that at this time in Western Volyn several congresses of Prosvita society were held, at which organizational issues were considered, action plans were developed for the development of Ukrainian schools, the expansion of Ukrainian book publishing, the establishment of libraries, and the fight against illiteracy. However, by the mid-1930s, the activities of Prosvita societies in Western Volyn were stopped by the efforts of the local authorities. Instead of them, «Prosvitianski Khaty» (educational homes) were spread, which were supposed to implement a pro-Polish cultural and educational policy among the Ukrainian population. Until 1928, a state of siege was maintained in Bukovyna, introduced by the Romanian authorities during the occupation of the region in November 1918. The «Ruska Besida» Society and its reading rooms in such conditions existed only on paper. Most of the branches and organizations were prohibited and closed. Closing of Ukrainian schools also took place, cultural and educational events were limited. After the dismissal of the state of siege, the activities of the «Ruska Besida» Society became somewhat more active. This was facilitated by the celebration of the 60th anniversary of the foundation of the society. However, the Romanian government tightly controlled any events organized by the society. In such conditions, it was never able to reach the pre-war level of activities. Nevertheless, even after the establishment of the fascist dictatorship in Romania in 1938, the society formally continued to exist. The Bolsheviks closed it down in 1940. It is also noted that in the ideological plan and in the most common forms of activities, Prosvita societies both in Volyn and Bukovyna were identical. Organizationally, the Bukovynian «Ruska Besida» was better structured, had a charter approved by the authorities, which clearly defined the goals and objectives of the society. One of the specific means of the struggle of the Polish authorities with the Ukrainian Prosvita societies in Western Volyn was the establishment of «ProsvitianskiKhaty», completely subordinate to the Polish authorities. In general, neither Prosvita societies in Volyn, nor «Ruska Besida» in Bukovyna could fully fulfill the tasks that the Ukrainian public set for themselves and demanded of them under the domination of foreign states.
Keywords: Західна Волинь; Буковина; Польща; Румунія; «Просвіта»; «Руська бесіда»; культурно- просвітня діяльність